Dampak Diskriminasi Kebijakan Perdagangan Sawit Uni Eropa Terhadap Perekonomian Indonesia - Muhammad (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Pasundan Bandung, 2023)
The European Union (EU) Parliamentary Resolution on Deforestation of Palm Oil and Tropical Forests was the catalyst for the severe problems currently facing the Indonesian palm oil industry. Delegated Regulation No. C (2019) 2055 Final on High and Low ILUC Risk Criteria in Biofuels was later adopted by the European Commission. Considering that Indonesian palm oil products comply with international law and sustainable development goals, this is considered a form of discrimination against palm oil with political motivation and corporate competition. Despite being one of the world's largest energy consumers, the European Union imports energy to meet its needs because natural resources in the region are insufficient. The European Union established the Renewable Energy Directive to promote the use and development of alternative energy sources, such as biofuels, in an effort to reduce its dependence on imported energy. Renewable energy sources produced from vegetable oils are known as biofuels. The purpose of this research is to determine how Indonesia will be affected by the discrimination or restrictions placed on oil palm cultivation by the European Union. The researcher adopts an attitude of economic diplomacy, and the fundamental premise is that the palm oil market must be closed to protect the environment. The research findings suggest that in order to overcome EU prejudice against Indonesian CPO products, the EU government and its citizens must be targeted by both key palm oil industry stakeholders and the Indonesian government.